Iceland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
The abolition of the fluctuation bands by the Icelandic government is seen as the final step of a consistent and gradual move toward increased exchange rate flexibility. Supplemented by the adoption of an inflation targeting regime, the new monetary policy framework should suit Iceland better. Iceland's new monetary policy framework has been introduced against a backdrop of a sound legal environment. The institutional and operational framework of the inflation targeting regime is well defined. The statistical data on the economic indices of Iceland are presented.